Heritability of some male reproductive traits in rabbit - Panella F.; Castellini C.; Facchin E. (Rabbit production in hot climates, 1994)
The quantitative and qualitative characteristics and the heritability of rabbit semen were evaluated. During the period 1991-93, 3670 semen samples were collected from 158 N.Z.W. bucks coming from a semen center and reared in four different rabbitries. The examined traits were the following: libido, ejaculate volume, spermatozoa/ml, motility, live sperms, fertility rate and litter size. The variability factors studied were: year, rabbitry, kindling order and buck. A different variability was observed for the semen traits: libido (mean
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)